The utilization of Trichoderma viride in Optimising Xylanase Production from Coffee Cherry Processing Waste - Nur Yudiastuti, Silvia Oktavia; Handayani, Wiwik; Novita Sari , Elok Kurnia; Wijaya, Rizza; Brilliantina, Aulia; Hasanuddin Slamet, Ahmad Haris (International Journal of Islamic Education, Research and Multiculturalism (IJIERM), 2024)
The use of enzymes in Indonesia is increasing rapidly and is used in various industries, especially FCMG. One of the enzymes that is widely used is xylanase, which is an extracellular enzyme that can hydrolyze xylan into xylose and xylo-oligosaccharides. This research aims to determine the optimum conditions for the xylanase production process from coffee cherry processing waste (CCPW) using Trichoderma viride through solid fermentation. The research method used was experimental using central composite design (CCD) in Design Expert 13.0 software. The treatment designs used were fermentation times of 24 hours, 48 ​​hours, and 72 hours; and substrate concentrations of 25%, 50%, and 75%. The experimental response analysis design was enzyme activity, protein content, and specific activity. The results of the research show that the optimum conditions for xylanase production are at a substrate concentration of 75% and a fermentation time of 24 hours with a desirability value of 0.742, which produces an enzyme activity value of 36.388 U/mL and a dissolved protein content of 0.494 mg/mL with a specific activity of 73.660. U/mg. The verification results show conformity with the formula predicted by the Design Expert 13.0 software, namely enzyme activity of 36,292 U/mL and protein content of 0.488 mg/mL with a specific activity of 74,369 U/mg